Use of Thai local vegetable extracts as natural preservatives in dried sausage system - Nanasombat, Suree; Armeen, Wanwisa; Arkom, Orawan (Pharmacognosy Communications)
Antioxidant and antimicrobial activities of Thai local vegetable extracts (three formulations) at the concentration of 0.02%, 0.1% and 0.2% in a Chinese-style sausage during storage at 4°C and 85% relative humidity (RH) for 20 days were evaluated. One of the three formulations of the extracts were Polygonum odoratum extract (PE) while the other two were mixed vegetable extracts of formulation 1 (MVE 1 ) and formulation 2 (MVE 2 ) which were the mixture of P. odoratum, Cassia siamea, Garcinia cowa and Limnophila aromatic extracts. All formulations of these vegetable extracts were able to delay lipid oxidation in the sausage. Addition of 0.2% vegetable extracts resulted in a greater decrease of TBARS value as compared to the other concentrations, but caused unacceptable color of the sausage. The vegetable extracts at 0.1% were selected for use in combination with 2.5% sodium lactate (SL) as preservatives in this sausage. Their effects on oxidative, microbial and sensory stability of sausage samples during storage at 4°C and 85% RH for 21 days were evaluated. These extracts were able to retard lipid oxidation by lowering TBARS value throughout the 21-day storage. Addition of 2.5% SL, either alone or in combination with 0.1% of these natural extracts resulted in decreasing number of total microbial counts in the samples. The total microbial counts in the samples added with SL alone, PE with SL, and MVE 2 with SL decreased by 1.36, 1.35, and 2.42 log units after 21 days of storage. However, addition of each vegetable extract alone did not result in reduction of total microbial counts in the sausages during storage. The sausage samples added with PE in combination with SL had less rancid odor compared to the samples of other treatments. Therefore, the vegetable extract, PE in combination with SL could be used to extend shelf-life of this sausage.
Keywords: antioxidant; antimicrobial; Polygonum odoratum; sodium lactate